Penyalahgunaan Teknologi Komputer untuk Tindakan Kriminal Siber dalam Novel Simvlacrm Karya Cassandra & Noorca Marendra Massardi - Awang Ihtisyamuddin; Fauzi Hartanto; Eva Dwi Kurniawan (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
This research aimed to explore information related to the misuse of computer technology for criminal activities in the novel Simvlacrm by Cassandra & Noorca Marendra Massardi. With the goal of preventing similar cybercriminal actions in real life, this research employed a descriptive method, involving activities such as reading, analyzing, and writing key points from the literary work. The primary findings encompass the misuse of computer technology as a tool for cybercrime, particularly in the forms of hoaxes and wiretapping. It is anticipated that this research will contribute to a deeper understanding of the potential risks of computer technology to cybersecurity